Literasi Digital dan dampaknya pada Intensi Berwirausaha: Studi Pada Mahasiswa Vokasi - Suryani, Sri; Chaniago, Harmon (Asosiasi Ahli Administrasi Indonesia, 2023)
The rapid development of technology and information encourages students such as Generation Z to enter the world of digital literacy, which is expected to make good use of it, especially in entrepreneurship. Hence, this study aims to determine the effect of Digital literacy on the entrepreneurship intentions of students majoring in Business Administration at Bandung State Polytechnic. The research method used in this study is a descriptive qualitative questionnaire measuring instruments. The number of respondents involved in this study was 311 students majoring in Business Administration at Bandung State Polytechnic. Then, for data analysis using SPSS v.20 by examining the validity and reliability test, and a simple regression analysis test. The results of the data analysis explain that Digital literacy has a positive and significant influence on the entrepreneurial intentions of students majoring in Business Administration at Bandung State Polytechnic.